Clara Cell 10 kDa Protein Alleviates Murine Hepatitis Virus Strain 3-Induced Fulminant Hepatitis by Inhibiting Fibrinogen-Like Protein 2 Expression - Yu, Haijing; Liu, Yang; Wang, Hongwu; Wan, Xiaoyang; Huang, Jiaquan; Yan, Weiming; Xi, Dong; Luo, Xiaoping; Shen, Guanxin; Ning, Qin (Frontiers in Immunology, 2018)
Background: Fulminant hepatitis (FH) is a serious threat to human life, accompanied by massive and rapid necroinflammation. Kupffer cells, the major immune cell population involved in innate immune responses, are considered to be central for FH. Fibrinogen-like protein 2 (Fgl2) is a pro-coagulant protein that is substantially induced in macrophages upon viral infection, and Fgl2 depletion represses murine hepatitis virus strain 3 (MHV-3) infection. Clara cell 10 kDa (CC10) protein is a secretory protein with anti-inflammatory properties in allergic rhinitis and asthma. However, its mechanisms of action and pathogenic roles in other disease are still unclear. In this study, we aimed to determine the role of CC10 in FH and the regulation of Fgl2 by CC10. Methods: A mouse FH model was established by peritoneal injection of MHV-3. The mice received CC10 protein through tail vein injection before viral infection. Survival rate, liver function, liver histology, fibrin deposition, and necrosis were examined. The regulatory effect of CC10 on Fgl2 expression was investigated using THP-1 cells and mouse peritoneal macrophages in vitro. Results: In the mouse FH model induced by MHV-3, the survival rate increased from 0 to 12.5% in the CC10 group compared to that in the saline-only control group. Meanwhile, the levels of ALT and AST in serum were significantly decreased and liver damage was reduced. Furthermore, hepatic Fgl2, TNF-α, and IL-1β expression was obviously downregulated together with fibrin deposition, and hepatocyte apoptosis was reduced after administration of CC10 protein. In vitro, CC10 was found to significantly inhibit the expression of Fgl2 in IFN-γ-treated THP-1 cells and MHV-3-infected mouse peritoneal macrophages by western blot and real-time PCR. However, there was no direct interaction between CC10 and Fgl2 as shown by co-immunoprecipitation. Microarray investigations suggested that HMG-box transcription factor 1 (HBP1) was significantly low in CC10-treated and IFN-γ-primed THP-1 cells. HBP1-siRNA treatment abrogated the inhibitory effect of CC10 on Fgl2 expression in HUVEC cells. Conclusion: CC10 protects against MHV-3-induced FH via suppression of Fgl2 expression in macrophages. Such effects may be mediated by the transcription factor HBP1.